ナンキョク カタバ フウタイ ミズホ キチ デノ シツド カンソク - 和田, 誠; ワダ, マコト; Wada, Makoto (1985)
P(論文) 極域気水圏観測の期間中の1979年から80年に, 湿度の長期観測をみずほ基地で行った。1979年の測器はパナメトリック社の酸化アルミニウムの電気容量を測定するタイプであり, 1980年はEG&G社の鏡面の霜を観測するタイプのものであった。低温でのこれらの測器の信頼度は必ずしも高くないが, ほぼ通年の観測から, 冬のみずほ基地では, 地上付近で少なくとも氷飽和の湿度になっている時が多いことが示唆された。 Two types of humidity sensors were available at Mizuho Station in 1979 and 1980. One was Panametric's hygrometer which measures the electric capacity of Al_2O_3 sensor, and the other was a mirror-type hygrometer made by EG&G. The result of humidity observations using these hygrometers suggests that the air at Mizuho Station in winter would be sometimes saturated in respect to ice. departmental bulletin paper